2020
DOI: 10.1093/geroni/igaa057.666
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prescription Opioid Use and Mortality in Community-Dwelling Older Adults

Abstract: Prescription opioid use is concerning among older adults. Yet, few studies have examined the impact of opioid use on mortality by considering multimorbidity. Our sample includes 1586 older adults aged ≥65 recruited in primary care from 2011-2013 in a large health administrative region in Quebec and participating in the ESA-Services study, a longitudinal study on aging and health service use. An opioid prescription delivered in the 3 years prior to the baseline interview was identified using the provincial phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This agrees with the findings of other reported studies, which have found similar results with increased risk of all-cause mortality. [18][19][20][21][22] In the bivariate Cox regression, we found that higher age, reduced cognitive function and disease burden were significantly associated along with being a CNSD user. Disease burden, reduced cognitive function and CNSD use are all factors that may be an expression of disease/ reduction in health, but in the multivariable analysis, adjusting for relevant covariates, we found only higher age and male sex to be factors associated with higher risk of mortality.…”
Section: Mortality and Use Of Opioids Z-hypnotics And Benzodiazepinesmentioning
confidence: 79%
See 3 more Smart Citations
“…This agrees with the findings of other reported studies, which have found similar results with increased risk of all-cause mortality. [18][19][20][21][22] In the bivariate Cox regression, we found that higher age, reduced cognitive function and disease burden were significantly associated along with being a CNSD user. Disease burden, reduced cognitive function and CNSD use are all factors that may be an expression of disease/ reduction in health, but in the multivariable analysis, adjusting for relevant covariates, we found only higher age and male sex to be factors associated with higher risk of mortality.…”
Section: Mortality and Use Of Opioids Z-hypnotics And Benzodiazepinesmentioning
confidence: 79%
“…This agrees with the findings of other reported studies, which have found similar results with increased risk of all-cause mortality. 18–22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations